Implementation of Computer Network Security Using Fortigate as a Firewall at the Computer Lab of IAIN Bengkulu - Dhanu Prima Jaya; Hari Aspriyono; Eko Suryana (Perkumpulan Dosen Muda (PDM) Bengkulu, 2021)
This study aims to secure the network by using Fortigate as Firewall on the server computer at computer lab of IAIN Bengkulu so that it can detect attacks, counter attack, and block the attacker's IP address to the server computer. The research method used is NDLC (Network Development Life Cycle). This method aims to analyze, implement and monitor the research method. Implementing Fortigate as a Firewall to secure the server computer in the event of ICMP Flooding attack and Port scanning aimed at the server computer so that it can be identified when an attack occurs and can avoid hangs on the server computer.